The challenges of integrating artificial intelligence applications and algorithms in the production of journalistic content (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to find out the level of awareness of experts about the possibility of integrating journalism into artificial intelligence algorithms, to find out whether there is a significant difference between experts and specialists in their awareness of the transformations that artificial intelligence algorithms may bring about, and to find out whether there is any significant difference between experts in their perception of professional practices. that can be performed by artificial intelligence algorithms. An open-ended questionnaire was used to collect data, which was distributed to a sample consisting of 178, to examine four hypotheses: that artificial intelligence algorithms in journalism are able to collect, analyse and formulate data in traditional journalistic templates and forms, that artificial intelligence algorithms will completely solve the tasks of a traditional journalist, that artificial intelligence algorithms in journalism will force changes in communication theories and structural construction of journalistic forms, Integrating AI algorithms into journalism shortens content production and marketing processes in no time. The study concluded with a set of results, the most important of which were: Artificial intelligence is still a new field for journalism, and within narrow limits, writing style is still the main component, and journalism needs human intervention when applying algorithms. Opinion differs about the changes that artificial intelligence applies to communication theories Infrastructure preparations will affect the acceleration of AI algorithms in journalism, sending and receiving.